Republic of Poland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2003)
This Selected Issues paper analyzes fiscal developments and the sustainability of the current fiscal stance in Poland. It analyzes fiscal risks and fiscal vulnerability by investigating the contingent liabilities of the government and by performing stress tests to gauge the exposure of the budget to fiscal risks. Using different approaches, the paper tries to determine the size of fiscal adjustment Poland needs to undertake to strengthen the fiscal position and to reduce exposure to fiscal risks to a more manageable level.